Once upon a tip... : a story of MOOCs and gamification - Bidarra, José (2017)
This paper discusses the future of MOOCs based on recent research and acknowledged affordances of videogame’s design. The interest in MOOCS for educational purposes has increased over the last few years, with researchers identifying key pedagogical features that make the success of these inherently powerful learning tools. However, low student motivation and high dropout rates have somehow changed the original expectations of many researchers, despite the MOOC user base doubling in 2015. So, in this study we survey recent literature looking for answers, and discuss the evidence gathered from specific MOOCs with over one thousand participants, namely, pioneering iMOOC courses at Universidade Aberta (the Portuguese Open University). Finally, we look at the gaming world and discuss some findings that may benefit the learning design of MOOCs, considering that, besides the huge appeal of these (free) courses, there are recurring shortcomings that we have to alleviate. We follow up on the tip that gamification, and other emerging strategies, such as social networking and digital storytelling, may be vital to assure a sustainable future for open education and MOOCs.